1998
DOI: 10.1002/(sici)1097-0177(199812)213:4<464::aid-aja11>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific expression of chickenSox2 in the developing gut and lung epithelium: Regulation by epithelial-mesenchymal interactions

Abstract: In situ analysis of the chicken cSox2 gene, a member of the transcription factor family containing an Sry-like high-mobility group (HMG) box, demonstrated localized expression in the embryonic endoderm. Transcripts of cSox2 appeared before commencement of morphogenesis and cytodifferentiation in the rostral gut epithelium from the pharynx to the stomach. The caudal limit of cSox2 expression coincided with that of the region competent for proventricular differentiation and to the rostral limit of the domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 55 publications
(58 reference statements)
5
108
1
Order By: Relevance
“…The staining was strongest in the basal cell layer and progressively decreased with maturing epithelium. Although SOX2 is not considered to 40 Our findings indicate that unlike its potential role as a cancer stem-like cell/ tumor-initiating cell marker in various cancers such as lung adenocarcinoma, 41 gastric carcinoma, 42 breast carcinoma, 43 head and neck squamous cell carcinomas, 44 and metastatic melanomas, 45 it does not appear to mediate regulation of progenitor cells of the folliculo-sebaceous unit or interfollicular epidermis from which basal cell carcinomas originate. 29 The differential expression of SOX2 not only allows for a reliable distinction between basal cell carcinomas and basaloid squamous cell carcinomas but also provides opportunities for selective therapeutic intervention in basaloid squamous cell carcinomas.…”
Section: Clinical Follow-upmentioning
confidence: 74%
“…The staining was strongest in the basal cell layer and progressively decreased with maturing epithelium. Although SOX2 is not considered to 40 Our findings indicate that unlike its potential role as a cancer stem-like cell/ tumor-initiating cell marker in various cancers such as lung adenocarcinoma, 41 gastric carcinoma, 42 breast carcinoma, 43 head and neck squamous cell carcinomas, 44 and metastatic melanomas, 45 it does not appear to mediate regulation of progenitor cells of the folliculo-sebaceous unit or interfollicular epidermis from which basal cell carcinomas originate. 29 The differential expression of SOX2 not only allows for a reliable distinction between basal cell carcinomas and basaloid squamous cell carcinomas but also provides opportunities for selective therapeutic intervention in basaloid squamous cell carcinomas.…”
Section: Clinical Follow-upmentioning
confidence: 74%
“…[28][29][30][31] It was recently suggested that several differentiation-associated genes such as NKX6.3, SOX2, CDX2, PDX1, and OCT1 have an important role in gastric differentiation and intestinal metaplastic formation. 32 SOX2 contributes to the development of foregut-derived organs, such as the esophagus and stomach, 33,34 and controls the expression of pepsinogen A and Muc5ac. 35,36 The expression of SOX2 is downregulated during the progression from incomplete to complete intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Sox2 was found to be expressed in early chick endodermal epithelium from pharynx to lung and stomach. 21 Other studies on human specimens showed that Sox2 is expressed in normal stomach epithelium, 22 and in cancers of endodermal origin tissues. 23 However, little is known about the role of Sox2 during endodermal differentiation.…”
Section: Discussionmentioning
confidence: 99%